A Paradigm of Sustainable Development at School - Galkutė, Laima (Acta Paedagogica Vilnensia, 2005)
The concept of sustainable development represents a new issue in the Lithuanian school system. A pilot project "School Agenda 21" was carried out in 2000- 2003 to encourage teachers in developing and implementing models of education for sustainable development at the school in connection with national education strategies. Activities included: integration of sustainable development and real life issues into school curriculum, the development of key competences for future professional and social activities, actions to promote changes of lifestyle towards mare sustainable one as well as participation in solving community problems. The project "School Agenda 21" was based on action research methodology emphasizing experiential learning, self-evaluation and participation in planning of project activities. The main conclusions of the project "School Agenda 21" are presented in the article.
Keywords: school; paradigm; sustainable development; national education strategy